Winning Our Freedoms Together : African Americans and Apartheid, 1945-1960 - Grant, Nicholas (Book collections on Project MUSE., 2017)
"In this transnational account of black protest, Nicholas Grant examines how African Americans engaged with, supported, and were inspired by the South African anti-apartheid movement. Bringing black activism into conversation with the foreign policy of both the U.S. and South African governments, this study questions the dominant perception that U.S.-centered anticommunism decimated black international activism. Instead, by tracing the considerable amount of time, money, and effort the state invested into responding to black international criticism, Grant outlines the extent to which the U.S. and South African governments were forced to reshape and occasionally reconsider their racial policies in the Cold War world." -- Publisher's description.